UNDRAINED BEARING CAPACITY OF EMBEDDED STRIP FOOTINGS UNDER VERTICAL AND HORIZONTAL LOADS - BENMEDDOUR, D.; YAHIA-CHERIF, H.; MELLAS, M. (Courrier du Savoir; Vol. 18 (2014): Courrier du Savoir)
This paper is concerned with the undrained bearing capacity of embedded strip footing under inclined loading (i.e. combined vertical and horizontal). A series of numerical computations using the finite-difference code Fast Lagrangian Analysis of Continua (FLAC) was carried out to evaluate the failure envelopes in vertical force – horizontal force (V-H) plane, using both probe and swipe analyses. The adopted approach involves a numerical solution of the equations governing elasto-plastic soils. The soil is modeled by an elasto-plastic model with a Tresca criterion. The results are presented in terms of the failure envelope in vertical and horizontal loading plane.